Untargeted metabolomics reveals links between Tiger nut (Cyperus esculentus L.) and its geographical origin by metabolome changes associated with membrane lipids. Issue 10 (3rd October 2018) - Rubert, Josep; Hurkova, Kamila; Stranska, Milena; Hajslova, Jana
ABSTRACT: Tiger nuts and tiger nut milk are well-known Valencian products, and step-by-step these tubers and the tuber-based beverage are becoming more and more relevant products in international markets. However, the increasing demand and success of Valencian tiger nuts did not allow protected designation of origin (PDO) tuber to supply the domestic and international markets. Therefore, the verification of the geographical origin is highly required. In this research, the main objective was to combine an advance analytical method and chemometrics tools in order to decipher the geographical origin of 45 tiger nut samples from (i) 'Xufa de València' PDO and (ii) African samples. The analytical method, based on solid-liquid extraction followed by ultra-high performance liquid chromatography coupled to high resolution tandem mass spectrometry (UHPLC-HRMS) metabolomics approach, highlighted sensitivity and wide linear dynamic range in order to simultaneously analyse polar and non-polar metabolites. After data processing, a pronounced sample clustering according to the geographical origin was clearly observed using unsupervised models, and supervised models revealed that tiger nuts lipidome was associated with the geographical origin. As a result, African samples highlighted an overexpression of phospholipids, such as phosphatidylethanolamine 34:1, and triacylgricerols crosslinked to environmental stress and alteration of membrane lipid compositions. GRAPHICAL ABSTRACT: